A Polymer Hole Extraction Layer for Inverted Perovskite Solar Cells from Aqueous Solutions. Issue 20 (25th July 2016) - Liu, Yao; Renna, Lawrence A.; Page, Zachariah A.; Thompson, Hilary B.; Kim, Paul Y.; Barnes, Michael D.; Emrick, Todd; Venkataraman, Dhandapani; Russell, Thomas P.
Abstract : Poly(Phenylene vinylene) anionic polyelectrolyte (PVBT‐SO3 ) was found to be an efficient hole extraction layer for inverted perovskite solar cells. It can be cast from an aqueous solution and does not require thermal annealing for improved device performance. The devices show maximum solar cell efficiency of 15.9% and exhibit improved stability under ambient conditions and enhanced charge extraction.